THE UTILIZATION OF WANYI SEEDS (Mangifera caesia Jack.) IN MAKING ETHANOL BY ENZYMATIC HYDROLYSIS AND FERMENTATION USING Saccharomyces cerevisiae - Arissah, Nur; Sitorus, Saibun; Gunawan, Rahmat (Jurusan Kimia FMIPA UNMUL, 2020)
The utilization of wanyi seeds (Mangifera caesia Jack.) in making ethanol by enzymatic hydrolysis and fermentation using Saccharomyces cerevisiae has been carried out. The method used is the hydrolysis of Î±-amylase and gluco-amylase enzymes, fermentation with time variation and yeast concentration as well as the addition of 0.5% urea nutrition and 0.06% NPK, distillation and gas chromatography. Ethanol content 98.508% at 6 days fermentation with yeast concentration 0.23%.